IPTEKS PENGGUNAAN E-BILLING WAJIB PAJAK PADA PT BANK SULUTGO - Wowor, Cindy Helena; Kumendong, Jannifer Vilisia; Nangoi, Grace B. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
In this increasingly developing era, a more active role is needed from taxpayers to calculate, deposit and report independently taxpayer tax obligations. Moreover, the largest regional bank company in the North Sulawesi and Gorontalo regions, namely PT Bank SulutGo, must follow the developments of the existing era where all have been based on technology.Â PT Bank SulutGo has been appointed as a perception bank on December 11, 2014 and uses an e-billing system launched by the Directorate General of Taxes so that tax payments are made easier.Keywords : e-billing PT Bank SulutGo the largest regional bank